A fabric tensor based small strain constitutive law for the elastoplastic behavior of snow. (February 2022) - Singh, Anurag K.; Srivastava, P.K.; Kumar, N.; Mahajan, P.
Abstract: The mechanical behavior of snow depends on its density and microstructure. The anisotropy in the microstructure is expressed in terms of fabric tensor that leads to an anisotropic stress-strain relation. Lately, fabric-based relations have successfully estimated the elastic properties of snow. Motivated by this, we propose a fabric-based macroscopic elasto-plastic constitutive law for snow, which can be used to study avalanche initiation. Mean Intercept Length tensor used as a measure of material fabric is determined by X-ray tomography. Fabric tensor and density-dependent yield surface with a provision for isotropic hardening/softening are used in this process. Beyond the initial yield, the yield function grows till the strength of the snow is reached and then softens. Since snow exhibits tension and compression behavior asymmetry, a piece-wise quadratic yield function is used. Stress-strain curves needed for determining the equation of the hardening/softening law and other parameters of the proposed macroscopic constitutive law are obtained through micro-Finite Element (μ-FE) simulations. The macroscopic constitutive law has been implemented as a user subroutine in a FE code and can predict the snow's multiaxial behavior. Highlights: A fabric tensor based small strain constitutive law (macroscopic law) for the elastoplastic behavior of snow based on its microstructure, is proposed. The microstructure is included in the form of a second-order fabric tensor. The stress-strain law is able to model the elasto-plastic and softening behavior of snow. The parameters of the macroscopic law are determined by comparison with the microstructure Finite Element method. The model has an advantage over existing models in being able to include anisotropy of the microstructure of snow.